Multifocal head and neck amyloidosis as a diagnostic clue of systemic lupus erythematosus (SLE): A case report. Issue 35 (August 2019) - Chen, Chih-Hao; Sun, Chuan-Hung
Abstract: Rationale: Amyloidosis accounts for 2% of head and neck tumors. Amyloidosis that develops in the head and neck region is localized amyloidosis. Multifocal amyloidosis in the head and neck region is extremely rare. Patient concerns: The patient presented to the clinic of otolaryngology with nasal obstruction, anosmia and left neck mass for several months. Diagnosis: A left nasopharynx tumor was revealed under nasopharyngeal scope. Eosinophilic, proteinaceous material was revealed under a pathology scope in the nasopharynx tissue and neck tumor. Congo red staining demonstrated pale congophilic amorphous material with apple-green birefringence under cross-polarized light, and multifocal amyloidosis was diagnosed. Amyloidosis secondary to systemic lupus erythematosus (SLE) was confirmed after a series of investigations. Interventions: The patient underwent local excision for multifocal amyloidosis without following management. To control underlying SLE, the patient accepted steroid pulse therapy and immunosuppressants. The patient eventually achieved disease remission. Outcomes: During the 6 months of follow-up in the outpatient department of otolaryngology and rheumatology, complications, recurrence of nasopharyngeal amyloidosis, and SLE flare-up were not observed. Lessons: Head and neck amyloidosis involving the nasopharynx is a rare presentation of this disease. Head and neck multifocal amyloidosis should be taken as a hint of systemic disease. In head and neck amyloidosis, a comprehensive survey should be performed to clarify the underlying disease predisposing to amyloidosis and organ involvement.